Anionic cyclometalated Pt(ii) and Pt(iv) complexes respectively bearing one or two 1, 2-benzenedithiolate ligands. Issue 33 (10th August 2018) - Ionescu, Andreea; Godbert, Nicolas; Aiello, Iolinda; Ricciardi, Loredana; La Deda, Massimo; Crispini, Alessandra; Sicilia, Emilia; Ghedini, Mauro
Abstract : The first examples of anionic Pt(IV) complexes were obtained through the addition of a second molecule of a ligand to the Pt(II) analogues. Abstract : Novel anionic cyclometalated Pt(ii ) square-planar complexes NBu4 [(C^N)Pt II (S^S)], containing 2-phenylpyridine H(PhPy), 2-(2, 4-difluorophenyl)-pyridine H(F2 PhPy) and benzo[ h ]quinoline H(Bzq), respectively, as a cyclometalated ligand and the dianionic 1, 2-benzenedithiolate (Thio) 2− fragment as an (S^S) ligand, were synthesised. By the simple addition of an equivalent of (Thio) 2− to the NBu4 [(C^N)Pt II (Thio)] complexes, octahedral anionic NBu4 [(C^N)Pt IV (Thio)2 ] analogues were obtained, representing, to the best of our knowledge, the first examples of Pt(iv ) anionic cyclometalated complexes. The molecular structures of the obtained complexes in the case of the NBu4 [(Bzq)Pt II (Thio)] and the NBu4 [(Bzq)Pt IV (Thio)2 ] complexes were confirmed by single crystal X-ray diffraction analysis. Furthermore, the electrochemical and photophysical properties of the two series of Pt(ii ) and Pt(iv ) newly synthesised complexes were studied and DFT and TD-DFT calculations were performed in order to comprehensively investigate the displayed behaviour. All Pt(ii ) and Pt(iv ) complexes show intense luminescence in the solid state, with remarkable enhancement of the emission quantum yields, proving to be excellent examples of aggregation-induced emission systems.